2007
DOI: 10.1111/j.1473-2165.2007.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

An overview of hair dye safety

Abstract: Summary Background  Due to their basic reactive chemistry, the safety evaluation of hair dyes has always been a major consideration. Hair dyes are therefore one of the most studied and regulated consumer products on the market with an overwhelming amount of safety data. Yet, hair dyes continue to come under scrutiny, primarily regarding two safety concerns: First, a potential link to increased cancer risk, and second, skin allergy. Aims  This paper will review epidemiologic studies regarding hair dye safety, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Several of them were legally banned in Europe (put on Annex II of the EU cosmetics directive). It was concluded that taken into account the restrictions no relevant cancer risk for actual hair dye users exist (121)(122)(123). This is confirmed by the present evaluation program performed in the SCCP where all hair dyes used are critically assessed based on state of the art safety dossiers.…”
Section: Exposure To the Hair Dye Contaminant 4aminobiphenylsupporting
confidence: 70%
“…Several of them were legally banned in Europe (put on Annex II of the EU cosmetics directive). It was concluded that taken into account the restrictions no relevant cancer risk for actual hair dye users exist (121)(122)(123). This is confirmed by the present evaluation program performed in the SCCP where all hair dyes used are critically assessed based on state of the art safety dossiers.…”
Section: Exposure To the Hair Dye Contaminant 4aminobiphenylsupporting
confidence: 70%
“…However, new colorant technologies that will deliver such benefits have yet to emerge (Schlatter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason hair colorants have been under regulatory scrutiny for many years and both regulators and manufacturers have introduced measures to increase allergy risk awareness of consumers, and to minimize such risks through provision of maximal use concentrations, specific warning labels and precise usage and safety instructions (Schlatter et al, 2007;Krasteva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Permanent hair dyeing can damage the hair shafts if a poorly formulated product is improperly applied to the hair. 4 Two chemical processes occur during permanent hair dye. First, oxidation of the melanin pigment occurs, lightening the natural hair color.…”
Section: Discussionmentioning
confidence: 99%